Optimalisasi Potensi UMKM Warung Makan UKM Berkah: Inovasi Pada Layanan dan Pemasaran - Dewi Franciska Amalia Putri; Marsha Afina Auliany; Rahemat Hidayat; Erlan Valdy; Burhanuddin; Zainuddin, Asrini (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M), Universitas Mulawarman, 2024)
ABSTRAK: The role of Micro, Small and Medium Enterprises (MSMEs) is very significant to the Indonesian economy, especially its contribution to GDP and also employment. Warung Makan UKM Berkah is one of the MSMEs in Samarinda City that also contributes to this. However, based on the results of field observations and interviews with business actors, there are several problems that hamper the potential of the business, including: Poor business branding, no menu list, promotional strategies that only rely on word of mouth (WOM), unattractive banner displays, and lack of information services related to catering and payment facilities. From these observations, PKM students of the Faculty of Economics & Business, Mulawarman University together with the owner of Warung Makan UKM Berkah formulated a work program that focuses on service and marketing innovation, through making banners, menu lists, business logos, catering box stamps, social media (Instagram), and business funding platforms for the business.